Psychological and environmental factors influencing resilience among Ukrainian refugees and internally displaced persons: a systematic review of coping strategies and risk and protective factors - Rizzi, Damiano; Ciuffo, Giulia; Landoni, Marta; Mangiagalli, Matteo; Ionio, Chiara (Frontiers in Psychology, 2023)
Background: There is much discussion in the literature about the link between traumatic events related to war and mental illness. However, in comparison, mental health has been more researched than protective factors such as coping methods, which are the primary factors to build resilience in these circumstances. This review examines the psychological and environmental elements that influence the resilience of Ukrainian refugees and IDPs by analysing coping strategies and risk and protective factors.A literature search was conducted on PsycINFO, Pubmed, Scopus and Science Direct, with 259 articles screened and 13 determined as eligible for inclusion. Inclusion criteria were: 1) studies on adult Ukrainian refugees and/or IDPs; 2) original, peer-reviewed studies; 3) studies written in English or Italian language. Single-case reports and qualitative studies were excluded, as well as those studies written in any other language, and any studies for which the full-text version could not be obtained (i.e. conference abstracts). Two reviewers independently reviewed titles and abstracts, reviewed relevant articles' full text, and extracted the data.Results: A diverse range of individual and socio-environmental risk and protective factors were identified, influencing the resilience of Ukrainian refugees and IDPs, as well as five main categories of coping strategies: emotion-focused strategies, problem-focused strategies, avoidance, faith-based strategies and the ones based on sense of belonging.Discussion: War trauma and associated stressors can lead to distressing physical and psychological reactions, which persist even after leaving the war zone. Many individual and socio-environmental risk factors, such as mental disorders, financial security, having relatives wounded or displaced and an unfamiliar environment could influence the risk and severity of psychological difficulties, emphasizing the importance of coping strategies, social connections, faith and cultural resilience.This systematic review underscores the complex range of coping strategies and factors influencing the resilience of Ukrainian refugees and IDPs. Social connections and inclusive community interventions play vital roles in improving their psychological well-being, while longitudinal studies.